Movement and afferent representations in human motor areas: a simultaneous neuroimaging and transcranial magnetic/peripheral nerve-stimulation study - Shitara, Hitoshi; Shinozaki, Tetsuya; Takagishi, Kenji; Honda, Manabu; Hanakawa, Takashi (Frontiers in Human Neuroscience, 2013)
Neuroimaging combined with transcranial magnetic stimulation (TMS) to primary motor cortex (M1) is an emerging technique that can examine motor-system functionality through evoked activity. However, because sensory afferents from twitching muscles are widely represented in motor areas the amount of evoked activity directly resulting from TMS remains unclear. We delivered suprathreshold TMS to left M1 or electrically stimulated the right median nerve (MNS) in 18 healthy volunteers while simultaneously conducting functional magnetic resonance imaging and monitoring with electromyography (EMG). We examined in detail the localization of TMS-, muscle afferent- and superficial afferent-induced activity in M1 subdivisions. Muscle afferent- and TMS-evoked activity occurred mainly in rostral M1, while superficial afferents generated a slightly different activation distribution. In 12 participants who yielded quantifiable EMG, differences in brain activity ascribed to differences in movement-size were adjusted using integrated information from the EMGs. Sensory components only explained 10-20% of the suprathreshold TMS-induced activity, indicating that locally and remotely evoked activity in motor areas mostly resulted from the recruitment of neural and synaptic activity. The present study appears to justify the use of fMRI combined with suprathreshold TMS to M1 for evoked motor network imaging.